2014
DOI: 10.5897/ajb2013.13434
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 24- epibrassinolide on in vitro shootlets regeneration via direct organogenesis of Phaseolus vulgaris L.

Abstract: This study aimed to optimize an in vitro shootlets regeneration system via direct organogenesis for Phaseolus vulgaris L. cv. Brunca using 24-epibrassinolide (24-Epi). The best medium for shootlets proliferation as well as growth parameters was MS supplemented with 2 mg L-1 TDZ + 0.1 mg L-1 24-Epi. Stem explants recorded the best results of shootlets proliferation percentage compared with leaf or root explants, respectively. MS medium supplemented with 2 mg L-1 TDZ + 0.1 mg L-1 24-Epi gave the best results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Apparently protein electrophoresis is an effective procedure for determination of genetic stability among different treatments, several studies revealed the reliability of this technique in identification of the genetic variations in date palm and many other plants [20], [23], [61], [34], [22], [48]. Genetic impact of different chemicals has been identified using protein SDS-PAGE electrophoresis including PGRs; hydrogen peroxide and sodium salts [38], [35], [29], [4], [51], [52].…”
Section: Resultsmentioning
confidence: 99%
“…Apparently protein electrophoresis is an effective procedure for determination of genetic stability among different treatments, several studies revealed the reliability of this technique in identification of the genetic variations in date palm and many other plants [20], [23], [61], [34], [22], [48]. Genetic impact of different chemicals has been identified using protein SDS-PAGE electrophoresis including PGRs; hydrogen peroxide and sodium salts [38], [35], [29], [4], [51], [52].…”
Section: Resultsmentioning
confidence: 99%